America's great debate : Henry Clay, Stephen A. Douglas, and the compromise that preserved the Union - Bordewich, Fergus M. (New York : Simon & Schuster, 2012)
Chronicles the 1850s appeals of Western territories to join the Union as slave or free states, profiling period balances in the Senate, Henry Clay's attempts at compromise, and the border crisis between New Mexico and Texas.
"A frenzy seized my soul" -- One bold stroke -- "Order! order! order!" -- That demon question -- Ultima thule -- One of nature's nobles -- "We have another epidemic" -- The city of magnificent intentions -- Deadlock -- The godlike Daniel -- A great soul on fire -- Wounded eagle -- "Secession! peaceful secession!" -- A higher law -- A man of unbounded confidence -- "He is not dead, sir!" -- "Let the assassin fire!" -- Filibusters -- A legislative saturnalia -- A pact with the devil -- "War, open war" -- "All is paralysis" -- The wreck of the Omnibus -- A steam engine in britches -- "Break your masters' locks!" -- "It is time we should act" -- Triumphs -- A scandalous outrage.
Includes bibliographical references (p. [403]-463) and index.
Keywords: Compromise of 1850.; Clay, Henry, -- 1777-1852.; Douglas, Stephen A. -- 1813-1861.; United States -- Politics and government -- 1815-1861.; Slavery -- United States -- History -- 19th century; United States -- History -- Civil War, 1861-1865 -- Causes